DEGRADASI ZAT WARNA NAPHTOL BLUE BLACK SECARA SONOLISIS DAN FOTOLISIS DENGAN PENAMBAHAN TIO2-ANATASE - -, Safni; -, Maizatisna; -, Zulfarman; Sakai, T. (Jurnal Riset Kimia, 2007)
ABSTRACTDegradation of naphtol blue black dye had been done by sonolysis and photolysis with adding anatase-TiO2. Sonolysis method were performed using an ultrasound with frequency 45 kHz, and photolysis using an irradiation of UV light l= 359 nm.  The optimum condition for degradation of 6 mg/L naphtol blue black by sonolysis with addition of 0.1000 g anatase-TiO2 were found at pH = 3.0 and temperature 30 ± 1°C.  Percentage of degradation at pH and temperature optimum was 65.20% within 120 minutes treatment.  Degradation of 6 mg/L naphtol blue black by photolysis with addition of 0.1000 g anatase-TiO2 was optimum at pH=3.0 and percentage of degradation was 68.72% within 120 minutes irradiation without stirring. The combine of sonolysis and photolysis method simultaneously for degradation of naphtol blue black dye by adding anatase-TiO2, achieved 92.51% degradation after 60 minutes treatment. Keywords : sonolysis, photolysis, naphtol blue black